Cytokines and neuron-specific proteins in pediatric viral encephalitis and convulsive syndrome. I. Viral encephalitis - L. A. Alekseeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Convulsive syndrome in children is manifested in the three forms: febrile convulsions in acute infections, symptomatic convulsions during acute neuroinfection, as well as onset of epilepsy requiring careful differentiation to prescribe adequate therapy. A threat of convulsive syndrome spreads beyond complications related to ongoing infection, because its development is associated with the risk of emerging symptomatic epilepsy in the future. Postencephalitic epilepsy developing in children within the first years after viral encephalitis has been specifically highlighted. A necessity to identify groups at risk of developing epilepsy gave a momentum to seek out for biomarkers of epileptogenesis reflecting the features of systemic and local inflammatory process in the central nervous system during the immune response to infection. Cytokines mainly mediating inflammation are currently examined being studied as candidate biomarkers of the risk of epilepsy. On the other hand, neuron-specific proteins known as inflammation biomarkers identified in various diseases of the central nervous system are being investigated to reveal brain cell injury in neuroinfections and epilepsy. Here we review publications assessing a potential to use inflammation biomarkers (cytokines and neuron-specific proteins) to diagnose and monitor pediatric neurological diseases associated with convulsive syndrome. The first part of the review describes the results of determining the inflammation biomarkers in the blood and cerebrospinal fluid during acute viral encephalitis/encephalopathy associated with various neurotropic viruses (herpes viruses, flaviviruses, enteroviruses). A significance of diverse biomarkers in predicting an outcome and long-term disease consequences are discussed.